RELEVANSI HUKUMAN TAKZIR DALAM FIKIH DENGAN HUKUMAN SEBAGAI ALAT PENDIDIKAN - U., M. Shabir (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
Constitutions or rules are implemented simply for human well-being, that is, to make possible human beings enjoy advantages at most and avoid any disorders. Those who disobey the rules will be sentenced. One model of punishment based on Islamic jurisprudence is “takzir”. At the implementation stage of this model, the government or the judge should take both the condition of the doers and their cases into consideration. This is because punishment plays an important role as educational instrument. Despite this, some experts on education disagree with physical punishment, but they recommend other humane ways. In the field of education, students are punished in order that they do not commit the same mistakes again. This is in accordance with “takzir” in that it educates the offenders not to recommit the same mistakes in the future.